2010
DOI: 10.1139/w10-056
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and dominance of yeast species in naturally fermented milk from the Tibetan Plateau of China

Abstract: To determine which yeasts are present in the naturally fermented milks of China, 69 samples made by the nomads of Tibet were collected from the Tibetan Plateau in China. From these samples, 225 strains of yeast were isolated and identified using conventional microbiological analysis and gene sequencing analysis of the D1/D2 domain of the large subunit (26S) ribosomal DNA. The results showed that the total concentration of yeasts in these samples ranged from 5.01 to 8.97 log10 colony-forming units (CFU)/mL (6.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 36 publications
5
27
0
1
Order By: Relevance
“…Yarrowia lipolytica has been identified, at lower frequencies, in a number of other dairy products: in milk of cow, ewe and water buffalo (Baroiller & Schmidt, 1990;Chen et al, 2010;Corbo et al, 2001;Suárez & Iñigo, 1982), in (traditionally) fermented milk products such as yoghurt, kefir, nunu and amasi (Akabanda et al, 2010;Bai et al, 2010;Fröhlich-Wyder, 2003;Gadaga et al, 2000;LourensHattingh & Viljoen, 2002;Rohm et al, 1992;Viljoen et al, 2003), as well as in butter, cream and margarine (Bours & Mossel, 1973;Lanciotti et al, 1992;Lopandic et al, 2006). In yoghurt, the use of Y. lipolytica in starter cultures, to support the growth of probiotic bacteria, has been considered (Lourens-Hattingh & Viljoen, 2002).…”
Section: Natural Occurrence Of Yarrowia Lipolytica In Foodmentioning
confidence: 99%
“…Yarrowia lipolytica has been identified, at lower frequencies, in a number of other dairy products: in milk of cow, ewe and water buffalo (Baroiller & Schmidt, 1990;Chen et al, 2010;Corbo et al, 2001;Suárez & Iñigo, 1982), in (traditionally) fermented milk products such as yoghurt, kefir, nunu and amasi (Akabanda et al, 2010;Bai et al, 2010;Fröhlich-Wyder, 2003;Gadaga et al, 2000;LourensHattingh & Viljoen, 2002;Rohm et al, 1992;Viljoen et al, 2003), as well as in butter, cream and margarine (Bours & Mossel, 1973;Lanciotti et al, 1992;Lopandic et al, 2006). In yoghurt, the use of Y. lipolytica in starter cultures, to support the growth of probiotic bacteria, has been considered (Lourens-Hattingh & Viljoen, 2002).…”
Section: Natural Occurrence Of Yarrowia Lipolytica In Foodmentioning
confidence: 99%
“…This method allows for microbial adaptation and natural selection of strains thriving in the food matrix. There are several players involved in spontaneous fermentations, and previous studies have reported isolation of various yeasts and/or bacteria from natural fermentations of e.g., cereal based foods (Hellström et al, 2010; Ogunremi et al, 2015; Todorov and Holzapfel, 2015), or from various milk (Gadaga et al, 2001; Mathara et al, 2004; Bai et al, 2010; Yun Li and Guoqing, 2015), or cheese (Fasoli et al, 2015) fermentations. The analyses of the microbiota associated to spontaneous fermentations allows the isolation of microorganisms possessing properties desirable for implementation in industrial food or feed processes.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies on yeast strains with probiotic properties have investigated their lipolytic and proteolytic properties (Psomas et al, 2001) and the positive effects on the expression of pro-inflammatory cytokine IL-1α (van der Aa Kühle et al, 2005), as well as production of several vitamins, bioactive peptides, and more (Czerucka et al, 2007; Fernandez et al, 2015). Other beneficial effects of introducing selected yeast strains in food processes are for example the ability of such strains to metabolize lactose as a way of producing low lactose dairy products for lactose intolerant consumers (Gadaga et al, 2001; Mathara et al, 2004; Bai et al, 2010; Yun Li and Guoqing, 2015) and yeast strains acting as antagonists toward spoilage or pathogenic microorganisms (Mufandaedza et al, 2006) to mention a few examples. However, for a microorganism to be considered as a probiotic, the ability to survive/pass through the harsh conditions of the gastrointestinal tract (low pH), in presence of ox bile and at a temperature of 37°C with maintained viability is often applied as a first assessment.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to highlight the presence of S. suaveolens and T. coremiiforme in Algerian Rayeb because few papers have reported their presence in fermented milk (Bai et al, 2010). Besides, no studies were carried out on the identification of yeasts from Algerian Rayeb.…”
Section: Physiological Biochemical and Molecular Identification Of Ymentioning
confidence: 99%